Proceedings of the 21st Annual International Conference on Supercomputing 2007
DOI: 10.1145/1274971.1274996
|View full text |Cite
|
Sign up to set email alerts
|

A study of process arrival patterns for MPI collective operations

Abstract: Process arrival pattern, which denotes the timing when different processes arrive at an MPI collective operation, can have a significant impact on the performance of the operation. In this work, we characterize the process arrival patterns in a set of MPI programs on two common cluster platforms, use a micro-benchmark to study the process arrival patterns in MPI programs with balanced loads, and investigate the impacts of different process arrival patterns on collective algorithms. Our results show that (1) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 13 publications
2
23
0
Order By: Relevance
“…For the larger class C, the imbalance factors are even larger. The gathered results on our platform confirm previous studies in [2,3] that processes arrive at collective sites at different times.…”
Section: Process Arrival Patternsupporting
confidence: 89%
See 4 more Smart Citations
“…For the larger class C, the imbalance factors are even larger. The gathered results on our platform confirm previous studies in [2,3] that processes arrive at collective sites at different times.…”
Section: Process Arrival Patternsupporting
confidence: 89%
“…However, recent studies [2,3] have shown that processes in real applications can arrive at the collective calls at different times. This imbalanced process arrival pattern can significantly affect the performance of the collective operations [2]. In addition, it has been found that different collective communication algorithms react differently to PAP [2].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations